Electron donor type photoelectric conversion material, photoelectric conversion element using the same, photosensor, and display device

A novel electron donor type photoelectric conversion material with a specific structure addresses the limitations of diketopyrrolopyrrole compounds by enhancing green light absorption and thermal stability, facilitating efficient photoelectric conversion.

JP2025011041APending Publication Date: 2025-01-23TORAY INDUSTRIES INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024101766
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-10
Filing Date
2024-06-25
Publication Date
2025-01-23

AI Technical Summary

Technical Problem

Existing diketopyrrolopyrrole compounds used in photoelectric conversion materials face challenges as low-molecular compounds for vacuum evaporation, lacking functionality as electron donors, especially for selectively absorbing green light, and have issues with thermal stability during vapor deposition.

Method used

Development of an electron donor type photoelectric conversion material with a specific structural formula that includes substituents to enhance absorption in the green light region, improve thermal stability, and function as a p-type semiconductor, utilizing a compound represented by general formula (1) with specific groups R1, R2, X1, X2, R3, and R4 to optimize crystallinity and conjugation.

Benefits of technology

The material achieves high sensitivity in the green light region with improved thermal stability, enabling effective use in photoelectric conversion layers and enhancing photoelectric conversion efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011041000001
    Figure 2025011041000001
  • Figure 2025011041000002
    Figure 2025011041000002
  • Figure 2025011041000003
    Figure 2025011041000003
Patent Text Reader

Abstract

To provide a photoelectric conversion material which has sensitivity in a green light region, has high heat resistance and is available as a p-type semiconductor in a photoelectric conversion layer.SOLUTION: An electron donor type photoelectric conversion material has a structure represented by the following general formula (1). In the formula, R1 and R2 are each independently selected from the group consisting of a hydrogen, a substituted or unsubstituted alkyl group, a substituted or unsubstituted cycloalkyl group, a substituted or unsubstituted aryl group, a substituted or unsubstituted heteroaryl group, and a ring structure between adjacent groups. X1 and X2 each independently represent an oxygen atom, a sulfur atom or a selenium atom. R3 and R4 are each independently a group represented by a specific general formula.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electron donor type photoelectric conversion material, and a photoelectric conversion element, an optical sensor and a display device using the same. [Background technology]

[0002] In recent years, the Internet of Things (IoT) and big data have been attracting attention, and the importance of sensing technology to acquire various data that supports them is increasing. There are various sensing technologies, but optical sensing is a highly useful sensing technology that can be deployed in a variety of applications, such as changing the sensing target by selecting the target wavelength.

[0003] Optical sensors generally comprise a photoelectric conversion element that converts light into electrical energy and a light-emitting element, and sense an object by irradiating the object with light from the light-emitting element and receiving the light that is transmitted through or reflected from the object with the photoelectric conversion element. Such optical sensors can obtain biometric information such as fingerprints, vein shapes, and blood oxygen levels by using, for example, green light, red light, or near-infrared light. Furthermore, by forming the substrate, light-emitting element, and light-receiving element mainly from organic materials, it is possible to configure a thin and flexible device (for example, see Non-Patent Document 1).

[0004] In general, diketopyrrolopyrrole compounds have been studied as photoelectric conversion materials used in photoelectric conversion elements such as organic solar cells (see, for example, Patent Documents 1 to 4). Diketopyrrolopyrrole compounds have the advantage that the absorption wavelength region can be designed to a desired range by selecting a substituent. [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] Science Advances, 2016, Vol. 2, p. e1501856 [Patent documents]

[0006] [Patent Document 1] International Publication No. 2014 / 050764 [Patent Document 2] JP 2008-166339 A [Patent Document 3] JP 2010-192782 A Summary of the Invention [Problem to be solved by the invention]

[0007] In recent years, in order to make displays larger, the trend is toward bezel-less displays, which reduce the edges (bezels) of the screen. As displays become bezel-less, there is a demand for photoelectric conversion materials that can provide sensing elements within the screen and selectively absorb, among the blue, green, and red light emitted from light-emitting elements, particularly green light, and that do not absorb blue and red light easily.

[0008] However, although the diketopyrrolopyrrole compounds described in Patent Documents 1 to 3 are used as low molecular weight compounds to fabricate organic devices by vacuum deposition, in forming a photoelectric conversion layer, their use as p-type semiconductors that act as electron donors and their ability to selectively absorb green light and exhibit photoelectric conversion effects have not been sufficiently studied, and there is also the issue of low thermal stability during deposition.

[0009] Therefore, an object of the present invention is to provide a photoelectric conversion material that has sensitivity in the green light region, has high heat resistance, and can be used as a p-type semiconductor in a photoelectric conversion layer. [Means for solving the problem]

[0010] The present invention has the following configuration. [1] An electron donor type photoelectric conversion material having a structure represented by the following general formula (1):

[0011] [ka]

[0012] In the above general formula (1), R 1 and R 2 are each independently selected from the group consisting of a hydrogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted cycloalkyl group, a substituted or unsubstituted aryl group, a substituted or unsubstituted heteroaryl group, and a ring structure between adjacent groups. X 1 and X 2 each independently represents an oxygen atom, a sulfur atom, or a selenium atom. R 3 and R 4 are each independently a group represented by the following general formula (2):

[0013] [ka]

[0014] In the above general formula (2), *** represents a bond to a carbon atom. R 5 ~R 11 are each independently selected from the group consisting of a hydrogen atom, an alkyl group, a cycloalkyl group, an alkoxy group, an alkylthio group, an amino group, an aryl group, a heteroaryl group, an aryl ether group, an aryl thioether group, a silyl group, and a ring structure between adjacent groups. These groups may further have a substituent. [2] In the general formula (2), R 5 and R 11 At least one of the above is a hydrogen atom. [3] In the general formula (1), R 1 and R 2are each independently selected from the group consisting of a substituted or unsubstituted alkyl group, a substituted or unsubstituted cycloalkyl group, a substituted or unsubstituted aryl group, a substituted or unsubstituted heteroaryl group, and a ring structure between an adjacent group. [4] A photoelectric conversion element having a photoelectric conversion layer between an anode and a cathode, which converts light into electrical energy, wherein the photoelectric conversion layer contains the electron donor-type photoelectric conversion material according to any one of [1] to [3]. [5] The photoelectric conversion element according to [4], wherein the photoelectric conversion layer further contains an electron acceptor type photoelectric conversion material. [6] An optical sensor having the photoelectric conversion element according to [4] or [5]. [7] A display device comprising the optical sensor according to [6] and an organic light-emitting element, and having a function of detecting biological information by utilizing light from the organic light-emitting element. [8] The display device according to [7], wherein the biometric information is fingerprint information. [9] The display device according to [7], wherein the biometric information is vein information. Effect of the Invention

[0015] According to the present invention, it is possible to provide a photoelectric conversion material that has sensitivity in the green light region, has high heat resistance, and can be used as a p-type semiconductor in a photoelectric conversion layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, the embodiments of the present invention will be described in detail. However, the present invention is not limited to the following embodiments, and can be modified in various ways depending on the purpose and application.

[0017] <Photoelectric conversion materials> The photoelectric conversion material according to the embodiment of the present invention is an electron donor type photoelectric conversion material. The electron donor type photoelectric conversion material refers to a material that has a property of easily donating excited electrons generated by photoexcitation of molecules to other molecules. For example, as described later, it exists as a pair with an electron donor type photoelectric conversion material (p-type organic semiconductor material) in a photoelectric conversion layer, and donates electrons to an electron acceptor material (n-type organic semiconductor material) that has the property of accepting electrons.

[0018] The photoelectric conversion material according to the embodiment of the present invention has a structure represented by the following general formula (1).

[0019] [ka]

[0020] In the above general formula (1), R 1 and R 2 are each independently selected from the group consisting of a hydrogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted cycloalkyl group, a substituted or unsubstituted aryl group, a substituted or unsubstituted heteroaryl group, and a ring structure between adjacent groups. 1 and X 2 R each independently represents an oxygen atom, a sulfur atom, or a selenium atom. 3 and R 4 are each independently a group represented by the following general formula (2):

[0021] [ka]

[0022] In the above general formula (2), *** represents a bond to a carbon atom. 5 ~R 11 are each independently selected from the group consisting of a hydrogen atom, an alkyl group, a cycloalkyl group, an alkoxy group, an alkylthio group, an amino group, an aryl group, a heteroaryl group, an aryl ether group, an aryl thioether group, a silyl group, and a ring structure between adjacent groups. These groups may further have a substituent.

[0023] In the general formula (1), R 1 and R 2 is a group that contributes to the crystallinity and deposition stability of the compound. From the viewpoint of producing an amorphous thin film that has high heat resistance and exhibits semiconductor properties, R 1 and R 2 is preferably selected from the group consisting of a substituted or unsubstituted alkyl group, a substituted or unsubstituted cycloalkyl group, a substituted or unsubstituted aryl group, a substituted or unsubstituted heteroaryl group, and a ring structure between the adjacent groups, and R 1 and R 2 are each independently selected from the group consisting of a substituted or unsubstituted alkyl group, a substituted or unsubstituted cycloalkyl group, a substituted or unsubstituted aryl group, a substituted or unsubstituted heteroaryl group, and a ring structure between adjacent groups. Among the substituents selected from the above, a substituted or unsubstituted alkyl group and a substituted or unsubstituted aryl group are particularly preferred.

[0024] In the general formula (1), R 3 and R 4 is a group that can extend the conjugated structure and thus contributes to the absorption wavelength. In order to selectively absorb green light, it is preferable to extend the conjugation in the structure represented by general formula (1). Therefore, in the present invention, R 3 and R 4 are each independently a group represented by general formula (2).

[0025] The group represented by the general formula (2) (in this case, called a β-naphthyl group or a 2-naphthyl group) is R 5 ~R 11 can have a substituent on R to better extend the conjugation length. 5 and R 11 It is preferable that at least one of R is a hydrogen atom. 5 and R 11By making at least one of the above groups a hydrogen atom, it is possible to extend the conjugation with the structure represented by general formula (1), thereby allowing the photoelectric conversion material according to the embodiment of the present invention to selectively absorb green light.

[0026] In addition, R 3 and R 4 When the group represented by formula (2) is replaced by an α-naphthyl group, the α-naphthyl group takes a twisted structure relative to the planar structure represented by formula (1), suppressing the extension of the conjugation length. As a result, the maximum absorption wavelength is shifted to a shorter wavelength, and it becomes impossible to selectively absorb green light.

[0027] From the viewpoint of deposition stability, R 5 ~R 11 are preferably each independently selected from the group consisting of a hydrogen atom, an alkyl group, an alkoxy group, an amino group, an aryl group, a heteroaryl group, and a ring structure formed between an adjacent group.

[0028] In addition, from the viewpoints of deposition stability and ease of synthesis, X 1 and X 2 are each preferably an oxygen atom.

[0029] In all of the above groups, the hydrogen atom may be a deuterium atom. The same applies to the compounds or partial structures thereof described below.

[0030] In addition, in the case where all of the above groups are substituted, the substituent is preferably an alkyl group, a cycloalkyl group, an alkoxy group, an alkylthio group, an aryl group, a heteroaryl group, an aryl ether group, an aryl thioether group, a hydroxyl group, a halogen, a cyano group, an amino group, or a silyl group, and more preferably a specific substituent that is preferred in the description of each substituent. Furthermore, these substituents may be further substituted with the above-mentioned substituents.

[0031] In addition, in all of the above groups, "unsubstituted" means that the atoms bonded to the target basic skeleton or functional group are only hydrogen atoms or deuterium atoms.

[0032] The alkyl group refers to a saturated aliphatic hydrocarbon group such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, or a tert-butyl group, which may be substituted or unsubstituted. If substituted, the additional substituent is not particularly limited, and examples thereof include an alkyl group, a halogen, an aryl group, and a heteroaryl group, which is also common to the following description. The number of carbon atoms in the alkyl group is not particularly limited, but is preferably 1 to 20, more preferably 1 to 8, in terms of availability and cost.

[0033] The cycloalkyl group refers to a saturated alicyclic hydrocarbon group, such as a cyclopropyl group, a cyclohexyl group, a norbornyl group, an adamantyl group, etc., which may be substituted or unsubstituted. The number of ring carbon atoms is not particularly limited, but is preferably in the range of 3 to 20.

[0034] The alkoxy group refers to a group in which an aliphatic hydrocarbon group is bonded via an ether bond, such as a methoxy group, an ethoxy group, or a propoxy group, and this aliphatic hydrocarbon group may be substituted or unsubstituted. The number of carbon atoms in the alkoxy group is not particularly limited, but is preferably in the range of 1 to 20.

[0035] An alkylthio group is an alkoxy group in which the oxygen atom of the ether bond is replaced with a sulfur atom. The hydrocarbon group of the alkylthio group may be substituted or unsubstituted. The number of carbon atoms in the alkylthio group is not particularly limited, but is preferably in the range of 1 to 20.

[0036] The aryl group may be either a single ring or a condensed ring, and may be, for example, an aromatic hydrocarbon group such as a phenyl group, a naphthyl group, a fluorenyl group, a benzofluorenyl group, a dibenzofluorenyl group, a phenanthryl group, an anthracenyl group, a benzophenanthryl group, a benzoanthracenyl group, a chrysenyl group, a pyrenyl group, a fluoranthenyl group, a triphenylenyl group, a benzofluoranthenyl group, a dibenzoanthracenyl group, a perylenyl group, or a helicenyl group. Among them, a phenyl group, a biphenyl group, a terphenyl group, a naphthyl group, a fluorenyl group, a phenanthryl group, an anthracenyl group, a pyrenyl group, a fluoranthenyl group, or a triphenylenyl group is preferred. The aryl group may be substituted or unsubstituted. Here, in the present invention, a group in which a plurality of phenyl groups are bonded via a single bond, such as a biphenyl group or a terphenyl group, is treated as a phenyl group having an aryl group as a substituent. The number of ring carbon atoms is not particularly limited, but is preferably in the range of 6 to 40, more preferably 6 to 30. In addition, in a phenyl group, when two adjacent carbon atoms in the phenyl group each have a substituent, these substituents may together form a ring structure.

[0037] The heteroaryl group may be either a single ring or a condensed ring, and examples thereof include a pyridyl group, a furanyl group, a thiophenyl group, a quinolinyl group, an isoquinolinyl group, a pyrazinyl group, a pyrimidyl group, a pyridazinyl group, a triazinyl group, a naphthyridinyl group, a cinnolinyl group, a phthalazinyl group, a quinoxalinyl group, a quinazolinyl group, a benzofuranyl group, a benzothiophenyl group, an indolyl group, a dibenzofuranyl group, a dibenzothiophenyl group, a carbazolyl group, a benzocaine group, and the like. It refers to a cyclic aromatic group having one or more atoms other than carbon and hydrogen, i.e., heteroatoms, in the ring, such as a rubazolyl group, a carbolinyl group, an indolocarbazolyl group, a benzofurocarbazolyl group, a benzothienocarbazolyl group, a dihydroindenocarbazolyl group, a benzoquinolinyl group, an acridinyl group, a dibenzoacridinyl group, a benzimidazolyl group, an imidazopyridyl group, a benzoxazolyl group, a benzothiazolyl group, and a phenanthrolinyl group. The heteroatom is preferably a nitrogen atom, an oxygen atom, or a sulfur atom. The heteroaryl group may be substituted or unsubstituted. The number of ring carbon atoms is not particularly limited, but is preferably 2 to 40, more preferably 2 to 30.

[0038] The aryl ether group refers to a group in which an aromatic hydrocarbon group is bonded via an ether bond, such as a phenoxy group, and the aromatic hydrocarbon group may be substituted or unsubstituted. The number of carbon atoms in the aryl ether group is not particularly limited, but is preferably in the range of 6 to 40.

[0039] The aryl thioether group is an aryl ether group in which the oxygen atom of the ether bond is replaced with a sulfur atom. The aromatic hydrocarbon group in the aryl thioether group may be substituted or unsubstituted. The number of carbon atoms in the aryl thioether group is not particularly limited, but is preferably in the range of 6 to 40.

[0040] The term "halogen" refers to an atom selected from fluorine, chlorine, bromine and iodine.

[0041] A cyano group is a group with the structure -C≡N, where it is the carbon atom that is attached to the other groups.

[0042] The amino group is a substituted or unsubstituted amino group. In the case of substitution, examples of the substituent include an aryl group, a heteroaryl group, a linear alkyl group, and a branched alkyl group. As the aryl group and the heteroaryl group, a phenyl group, a naphthyl group, a pyridyl group, and a quinolinyl group are preferable. These substituents may be further substituted. The number of carbon atoms is not particularly limited, but is preferably 2 to 50, more preferably 6 to 40, and particularly preferably 6 to 30.

[0043] The silyl group refers to a group to which a substituted or unsubstituted silicon atom is bonded, and includes, for example, alkylsilyl groups such as trimethylsilyl, triethylsilyl, tert-butyldimethylsilyl, propyldimethylsilyl, and vinyldimethylsilyl, and arylsilyl groups such as phenyldimethylsilyl, tert-butyldiphenylsilyl, triphenylsilyl, and trinaphthylsilyl. The substituent on silicon may be further substituted. The number of carbon atoms in the silyl group is not particularly limited, but is preferably in the range of 1 to 30.

[0044] An example of the compound having a pyrromethene skeleton represented by general formula (1) is shown below, but is not limited thereto.

[0045] [ka]

[0046] [ka]

[0047] [ka]

[0048]

change

[0049]

change

[0050]

change

[0051]

change

[0052]

change

[0053]

change

[0054]

change

[0055]

change

[0056]

change

[0057]

change

[0058]

change

[0059]

change

[0060]

change

[0061]

change

[0062]

change

[0063]

change

[0064]

change

[0065]

change

[0066]

change

[0067]

change

[0068]

change

[0069]

change

[0070] [ka]

[0071] [ka]

[0072] [ka]

[0073] [ka]

[0074] [ka]

[0075] [ka]

[0076] Compounds having a skeleton represented by general formula (1) can be produced by referring to the methods described in, for example, Chemische Berichte, vol. 120, pp. 1075-1078 (1987) and Tetrahedron, vol. 58, No. 27, pp. 5547-5565 (2002).

[0077] The compound represented by the general formula (1) is preferably purified by organic synthesis such as recrystallization or column chromatography, and then further purified by heating under reduced pressure, generally called sublimation purification, to remove low boiling point components and improve the purity. The heating temperature in the sublimation purification is not particularly limited, but is preferably 330° C. or less, more preferably 300° C. or less, from the viewpoint of preventing thermal decomposition of the compound. The purity of the compound obtained by purification is preferably 99% by weight or more, from the viewpoint of stabilizing the device characteristics.

[0078] In the absorption spectrum of the compound having the skeleton represented by the general formula (1), the peak wavelength is preferably 480 nm or more and 580 nm or less from the viewpoint of increasing the absorption intensity of green light. -5 It can be measured using a UV-Vis spectrophotometer using a diluted solution of mol / L.

[0079] <Photoelectric conversion element> The photoelectric conversion element according to the embodiment of the present invention is a photoelectric conversion element in which a photoelectric conversion layer is present between an anode and a cathode and which converts light into electrical energy, and the photoelectric conversion layer contains the above-mentioned electron donor type photoelectric conversion material.

[0080] The photoelectric conversion layer preferably contains two or more types of photoelectric conversion materials, and for example, it is preferable to use a photoelectric conversion material having a structure represented by general formula (1) as an electron donor type photoelectric conversion material (p-type organic semiconductor) having electron donating properties, and combine it with an electron acceptor type photoelectric conversion material (n-type organic semiconductor) having electron accepting properties as a pair. That is, it is more preferable that the photoelectric conversion layer contains an electron donor type photoelectric conversion material having a structure represented by general formula (1) (hereinafter, sometimes simply referred to as "electron donor material") and an electron acceptor type photoelectric conversion material (hereinafter, sometimes simply referred to as "electron acceptor material").

[0081] The electron donor material and the electron acceptor material have different HOMO-LUMO levels. As described above, by combining an electron donor type photoelectric conversion material having a structure represented by general formula (1) with an electron acceptor material having different HOMO-LUMO levels, the excitons generated by absorbing light are efficiently charge separated and dissociated at the interface between the different materials, and the photoelectric conversion efficiency can be further improved. From the viewpoint that electrons flow to lower energy levels in photoelectric conversion elements, the electron donor material is selected from the group consisting of an electron donor material having a lowest unoccupied orbital (LUMO) of its lowest unoccupied orbital (LUMO) of the electron donor material. D The absolute value of is the LUMO of the electron acceptor material. A is equal to or smaller than the absolute value of (LUMO D ≦LUMO A However, depending on the voltage applied to the photoelectric conversion element, the LUMO D >LUMO A In some cases, the photoelectric conversion effect can be observed even under these conditions. D >LUMO A When D and LUMO A The difference between them is preferably 1 eV or less, and more preferably 0.5 eV or less.

[0082] Examples of the electron acceptor material include 1,4,5,8-naphthalenetetracarboxylic dianhydride (NTCDA), 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA), 3,4,9,10-perylenetetracarboxylic bisbenzimidazole (PTCBI), N,N'-dioctyl-3,4,9,10-naphthyltetracarboxydiimide (PTCDI-CH); 2-(4-biphenylyl)-5-(4-t-butylphenyl)-1,3, Examples of the compound include oxazole derivatives such as 4-oxadiazole (PBD) and 2,5-di(1-naphthyl)-1,3,4-oxadiazole (BND), triazole derivatives such as 3-(4-biphenylyl)-4-phenyl-5-(4-t-butylphenyl)-1,2,4-triazole (TAZ), phenanthroline derivatives, phosphine oxide derivatives, fullerene compounds, carbon nanotubes (CNT), and derivatives in which a cyano group is introduced into a poly-p-phenylene vinylene polymer (CN-PPV). Two or more of these may be used.

[0083] Among them, fullerene compounds are preferably used because they have a high charge separation rate and electron transfer rate. Examples of fullerene compounds include unsubstituted fullerenes such as C60, C70, C76, C78, ​​C82, C84, C90, and C94, [6,6]-phenyl C61 butyric acid methyl ester ([6,6]-PCBM), [5,6]-phenyl C61 butyric acid methyl ester ([5,6]-PCBM), [6,6]-phenyl C61 butyric acid hexyl ester ([6,6]-PCBH), [6,6]-phenyl C61 butyric acid dodecyl ester ([6,6]-PCBD), phenyl C71 butyric acid methyl ester (PC70BM), and phenyl C85 butyric acid methyl ester (PC84BM).

[0084] The photoelectric conversion layer may further contain an electron donor material other than the electron donor photoelectric conversion material having the structure represented by general formula (1). In this case, examples of the electron donor material include oligothiophene compounds such as boron dipyrromethene, terthiophene, quarterthiophene, sexithiophene, and octithiophene, phenylene vinylene compounds, p-phenylene compounds, polyfluorene compounds, phthalocyanine derivatives such as H2 phthalocyanine (H2Pc), copper phthalocyanine (CuPc), and zinc phthalocyanine (ZnPc), porphyrin derivatives, triarylamine derivatives such as N,N'-diphenyl-N,N'-di(3-methylphenyl)-4,4'-diphenyl-1,1'-diamine (TPD) and N,N'-dinaphthyl-N,N'-diphenyl-4,4'-diphenyl-1,1'-diamine (NPD), and carbazole derivatives such as 4,4'-di(carbazol-9-yl)biphenyl (CBP). Two or more of these may be used.

[0085] When the photoelectric conversion layer contains two or more types of photoelectric conversion materials, these materials may be mixed in a single layer, or layers containing each photoelectric conversion material may be stacked, but from the viewpoint of rectification, it is preferable that the layers are stacked.

[0086] In the case of stacking, it is preferable that the layer containing the electron donor material is located on the anode side, and the layer containing the electron acceptor material is located on the cathode side. In addition, in the case of stacking, a mixed layer (i-layer) may be present at the stacking interface. This type of configuration is called a pin structure, in which the i-layer is mainly responsible for charge separation, and the p-layer and n-layer are mainly responsible for hole transport and electron transport, respectively, thereby further increasing the photoelectric conversion efficiency.

[0087] In the case where they are mixed, it is preferable that the photoelectric conversion material having the structure represented by general formula (1) and the material to be combined are compatible at the molecular level or are phase-separated at the nano level. In the case where they are phase-separated, the domain size of the phase-separated structure is preferably 1 nm or more and 50 nm or less.

[0088] The thickness of the photoelectric conversion layer is preferably 10 nm to 500 nm, more preferably 20 nm to 100 nm. When the photoelectric conversion layer has a laminated structure, the thickness of the layer containing the photoelectric conversion material having the structure represented by general formula (1) and the thickness of the laminated layer are each preferably 5 nm to 495 nm, more preferably 10 nm to 50 nm, out of the total thickness of the photoelectric conversion layer. When a mixed layer (i layer) is present at the laminate interface, the thickness of the i layer is preferably 1 nm to 100 nm, more preferably 5 nm to 50 nm.

[0089] In the photoelectric conversion element, it is preferable that the anode and / or cathode have light transparency. The light transparency of the electrodes is not particularly limited as long as it is sufficient for incident light to reach the photoelectric conversion layer and generate an electromotive force. Here, the light transparency is defined as the light transmission characteristic of the electrode, which is expressed by the transmitted light intensity (W / m 2 ) / incident light intensity (W / m 2 )]×100(%) (this is called "light transmittance"). In the present invention, the light transmittance is preferably 50% or more, more preferably 70% or more, and even more preferably 90% or more at wavelengths of 350 nm or more. The thickness of the light-transmitting electrode may be in a range that has light transmittance and electrical conductivity, and varies depending on the electrode material, but is preferably 20 nm to 300 nm. The other electrode does not necessarily need to be light-transmitting as long as it is electrically conductive, and there is no particular limitation on the thickness.

[0090] As materials used for the electrodes, it is preferable to use a conductive material with a large work function for one electrode and a conductive material with a small work function for the other electrode.

[0091] When electrodes are made of different materials, an electrode made of a conductive material with a large work function is preferably used as the anode. Examples of conductive materials with a large work function include metals such as gold, platinum, chromium, and nickel, as well as transparent metal oxides such as indium, tin, and molybdenum, and composite metal oxides such as indium tin oxide (ITO) and indium zinc oxide (IZO).

[0092] Here, the conductive material used for the anode is preferably one that forms an ohmic junction with the photoelectric conversion layer. Furthermore, as described below, in the case where a hole transport layer is provided between the anode and the photoelectric conversion layer, the conductive material used for the anode is preferably one that forms an ohmic junction with the hole transport layer.

[0093] The method for forming the anode can be selected optimally depending on the material for forming the anode, and examples of the method include sputtering, vapor deposition, inkjet printing, etc. For example, when the anode is formed of a metal oxide, the sputtering method is preferably used, and when the anode is formed of a metal, the vapor deposition method is preferably used.

[0094] When electrodes are made of different materials, an electrode using a conductive material with a small work function is preferably used as a cathode. As conductive materials with a small work function, for example, alkali metals such as lithium, alkaline earth metals such as magnesium and calcium, tin, silver, aluminum, and alloys thereof are preferably used. A laminate using two or more of these materials may also be used.

[0095] Here, the conductive material used for the cathode is preferably one that forms an ohmic junction with the photoelectric conversion layer. Furthermore, as described below, in the case where an electron transport layer is provided between the cathode and the photoelectric conversion layer, the conductive material used for the cathode is preferably one that forms an ohmic junction with the electron transport layer. Moreover, it is also possible to improve the extraction current by introducing a metal fluoride such as lithium fluoride or cesium fluoride into the interface between the cathode and the electron transport layer.

[0096] The method for forming the cathode can be selected optimally depending on the material for forming the cathode, and examples of the method include sputtering, vapor deposition, inkjet printing, etc. For example, the sputtering method is preferably used when the cathode is made of a metal oxide, and the vapor deposition method is preferably used when the anode is made of a metal.

[0097] In order to maintain the mechanical strength of the photoelectric conversion element, suppress thermal deformation, and impart a barrier property that suppresses the intrusion of water vapor and oxygen into the photoelectric conversion layer, it is preferable to form the photoelectric conversion element on a substrate. Examples of the substrate include a glass plate, a ceramic plate, a resin film, a resin thin film obtained by curing varnish, and a metal thin plate. Among these, a glass substrate is preferably used from the viewpoint of transparency and ease of processing. In addition, flexible displays and foldable displays are increasing mainly in mobile devices such as smartphones, and resin films and resin thin films are suitable for this purpose, for example, heat-resistant films such as polyimide films and polyethylene naphthalate films.

[0098] The photoelectric conversion element according to the embodiment of the present invention may have a hole transport layer between the anode and the photoelectric conversion layer. Examples of materials for forming the hole transport layer include the above-mentioned oligothiophene compounds, phenylenevinylene compounds, p-phenylene compounds, polyfluorene compounds, phthalocyanine derivatives such as H2 phthalocyanine (H2Pc), copper phthalocyanine (CuPc), and zinc phthalocyanine (ZnPc), porphyrin derivatives, triarylamine derivatives such as N,N'-diphenyl-N,N'-di(3-methylphenyl)-4,4'-diphenyl-1,1'-diamine (TPD) and N,N'-dinaphthyl-N,N'-diphenyl-4,4'-diphenyl-1,1'-diamine (NPD), carbazole derivatives such as 4,4'-di(carbazol-9-yl)biphenyl (CBP), and metal oxides exhibiting p-type semiconductor properties such as molybdenum oxide and tungsten oxide. The thickness of the hole transport layer is preferably from 1 nm to 200 nm, and more preferably from 5 nm to 100 nm.

[0099] Furthermore, the photoelectric conversion element according to the embodiment of the present invention may have a hole extraction layer between the anode and the hole transport layer. Examples of materials for forming the hole extraction layer include charge transfer complexes such as tris(4-bromophenyl)aminium hexachloroantimonate (TBPAH), 1,4,5,8,9,11-hexaazatriphenylene-hexacarbonitrile (HAT-CN6), 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F4-TCNQ), tetracyanoquinodimethane derivatives, radialene derivatives, and fluorinated copper phthalocyanine.

[0100] In addition, the photoelectric conversion element according to the embodiment of the present invention may have an electron transport layer between the photoelectric conversion layer and the cathode. Examples of materials for forming the electron transport layer include the above-mentioned n-type organic semiconductors, as well as various metal complexes such as polycyclic aromatic derivatives, styryl aromatic ring derivatives, quinone derivatives, phosphorus oxide derivatives, quinolinol complexes such as tris(8-quinolinolato)aluminum(III), benzoquinolinol complexes, hydroxyazole complexes, azomethine complexes, tropolone metal complexes, and flavonol metal complexes.

[0101] From the viewpoint of further improving the electron transport efficiency, it is preferable to use a compound having a heteroaryl group containing electron-accepting nitrogen in the electron transport layer. Here, the electron-accepting nitrogen refers to a nitrogen atom that forms a multiple bond with an adjacent atom. The heteroaryl group containing electron-accepting nitrogen has a large electron affinity, so that it is easy to transport electrons, and contributes to improving the photoelectric conversion efficiency.

[0102] Examples of compounds having a heteroaryl group structure containing electron-accepting nitrogen include pyridine derivatives, triazine derivatives, pyrazine derivatives, pyrimidine derivatives, quinoline derivatives, quinoxaline derivatives, quinazoline derivatives, naphthyridine derivatives, benzoquinoline derivatives, phenanthroline derivatives, imidazole derivatives, oxazole derivatives, thiazole derivatives, triazole derivatives, oxadiazole derivatives, thiadiazole derivatives, benzimidazole derivatives, benzoxazole derivatives, benzthiazole derivatives, phenanthroimidazole derivatives, oligopyridine derivatives such as bipyridine and terpyridine, etc. Two or more of these may be used.

[0103] In addition, it is more preferable that the electron transport material has a condensed polycyclic aromatic skeleton, since the glass transition temperature is improved and the electron mobility is large. As such a condensed polycyclic aromatic skeleton, a quinolinol complex, a triazine derivative, a fluoranthene skeleton, an anthracene skeleton, a pyrene skeleton, or a phenanthroline skeleton is preferable.

[0104] The electron transport layer may contain an electron donor material. Here, the electron donor material is a compound that improves the electrical conductivity of the electron transport layer. Preferred examples of the electron donor material include alkali metals such as Li, inorganic salts containing alkali metals such as LiF, complexes of alkali metals and organic substances such as lithium quinolinol, alkaline earth metals, inorganic salts containing alkaline earth metals, complexes of alkaline earth metals and organic substances, rare earth metals such as Eu and Yb, inorganic salts containing rare earth metals, complexes of rare earth metals and organic substances, etc. Two or more of these may be used. Among these, metallic lithium, rare earth metals, and lithium quinolinol (Liq) are preferred.

[0105] The thickness of the electron transport layer is preferably from 1 nm to 200 nm, and more preferably from 5 nm to 100 nm.

[0106] The method for forming each of the layers constituting the photoelectric conversion element may be any of a dry process or a wet process, and examples of such methods include resistance heating deposition, electron beam deposition, sputtering, molecular lamination, coating, inkjet, printing, etc. Among these, resistance heating deposition is preferred from the viewpoint of element characteristics.

[0107] The photoelectric conversion element according to the embodiment of the present invention has a function of converting light into electrical energy. From the viewpoint of highly efficient photoelectric conversion of green light having different wavelengths, the photoelectric conversion element according to the embodiment of the present invention has an absorption spectrum of the photoelectric conversion layer, preferably having an absorption peak wavelength of 480 nm to 580 nm and a half width of 30 nm to 140 nm, more preferably having an absorption peak wavelength of 500 nm to 570 nm and a half width of 35 nm to 130 nm.

[0108] <Optical sensor> The photoelectric conversion element according to the embodiment of the present invention can be applied to various electronic devices and optical sensing devices that utilize the function of selectively and efficiently converting green light into electric signals. For example, it can be used as an optical sensor, an optical switch, and an image sensor, and can obtain biological information such as fingerprints, veins, pulse waves, and blood oxygen concentration with high sensitivity.

[0109] The biological information in the present invention is not particularly limited as long as it is information obtained from a living body, but examples of the biological information include information obtained as reflected or transmitted light by irradiating a living body with radiant light, and information obtained as light emitted from a living body. In addition, objects to be measured include, in addition to the above-mentioned fingerprints, veins, pulse waves, and blood oxygen concentration, for example, irises, face shapes, skin dryness, and blood sugar levels.

[0110] In recent years, many communication devices with display functions, such as mobile phones and tablet terminals, have been equipped with biometric authentication functions to improve security functions, and the optical sensor of the present invention is preferably used as a fingerprint authentication device for a display device. One aspect of the device is a display device that uses a combination of an optical sensor according to an embodiment of the present invention and an organic light-emitting element, and performs fingerprint authentication using light from the organic light-emitting element. For example, a fingerprint authentication function can be imparted to an organic EL display by forming part of pixels of the organic EL display that displays in a matrix and / or segment format with the photoelectric conversion element of the present invention.

[0111] As described above, the photosensor according to the embodiment of the present invention has excellent photoelectric conversion characteristics for green light, and therefore, when used in combination with a green light source, sensing can be performed with high accuracy and sensitivity.

[0112] For example, fingerprint information can be obtained with high accuracy by receiving and photoelectrically converting green light emitted from an organic light-emitting element of an organic EL display, which is reflected and scattered by a finger touching the display, using an optical sensor according to an embodiment of the present invention.

[0113] Furthermore, by configuring some of the pixels of an organic EL display with the optical sensor according to the embodiment of the present invention as described above, it is possible to impart a biosensing function to the organic EL display. That is, by receiving and photoelectrically converting the green light emitted from the organic light emitting element of the organic EL display, which is absorbed and scattered by a finger touching the display, with the photoelectric conversion element of the present invention, it is possible to obtain biological information such as veins, pulse waves, and blood oxygen concentration with high accuracy.

[0114] The compound according to the embodiment of the present invention includes a compound having a structure represented by the following formula (3).

[0115] [ka]

[0116] In formula (3), R 12 ~R 21 are each independently selected from the group consisting of a hydrogen atom, an alkyl group, and an alkoxy group.

[0117] The compound represented by the above formula (3) is a material that achieves both deposition stability and heat resistance of a thin film, and can be used for applications such as organic light-emitting devices, organic transistors, organic thin-film solar cells, and biosensors, in addition to the optical sensors described above. EXAMPLES

[0118] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.

[0119] First, the evaluation methods used in the examples and comparative examples will be described below.

[0120] ( 1 H-NMR) The compounds obtained in the examples were analyzed in deuterated chloroform solution using a superconducting FT-NMR JNM-ECZ400R (manufactured by JEOL Ltd.). 1 The chemical structure was identified by H-NMR measurement.

[0121] (Thin film absorption characteristics) A 3 cm square quartz plate was surface-cleaned for 10 minutes using a UV ozone cleaner (manufactured by Sen Special Light Sources). Then, using a vapor deposition machine, the pyrromethene boron complex obtained in each Example and the pyrromethene obtained in the Comparative Example were vapor-deposited at a film-forming rate of 10 nm / s to produce a thin film with a thickness of 30 nm. The absorption spectrum of the obtained thin film was measured using a spectrophotometer (U-3010) manufactured by Hitachi High-Tech Science Co., Ltd., and the peak wavelength and half-width were obtained.

[0122] In addition, a tangent line was drawn to the falling edge on the long wavelength side of the obtained absorption spectrum, and the wavelength value λedge [nm] at the intersection point between the tangent line and the horizontal axis was substituted into the following conversion formula 2 to calculate the energy gap Eg. Conversion formula 2: Eg[eV]=1239.85 / λedge In addition, the absorbance A and film thickness x obtained from the absorption spectrum were substituted into the following conversion formula 3 to obtain the absorption coefficient α. Conversion formula 3: α[m -1 ]=A / log 10 (e / x)[m].

[0123] (Spectral sensitivity peak measurement) For the optical sensors obtained in each of the Examples and Comparative Examples, monochromatic light with wavelengths from 400 nm to 700 nm at 1 nm intervals was irradiated from the glass substrate side in the atmosphere, and the external quantum efficiency and the spectral sensitivity peak wavelength at -3 V were measured using a spectral sensitivity measuring device (Hyper Monolight System, SM-250 model, manufactured by Bunkoukeiki Co., Ltd.).

[0124] Example 1 Synthesis of Compound A-1 The following reaction was carried out under a nitrogen atmosphere. Compound A-1B (23.6 g) and potassium tert-butoxide (16.1 g) were dissolved in tert-butyl alcohol (60 mL) and stirred at 120°C for 2.5 hours. A-1A (14.6 mL) dissolved in tert-butyl alcohol (12 mL) was added, and the mixture was stirred at 120°C for 8.5 hours. The reaction solution was cooled to room temperature, and acetic acid (9 mL) dissolved in methanol (60 mL) was added to quench the reaction. The precipitated solid was filtered and washed with methanol to obtain 14.1 g (51%) of compound A-1C.

[0125] The following reaction was carried out under a nitrogen atmosphere. Compound A-1C (2.52 g) obtained above and potassium tert-butoxide (1.82 g) were dissolved in dimethylformamide (65 mL), iodomethane (1.02 mL) was added, and the mixture was stirred at 80° C. for 6 hours. After cooling to room temperature, the solid precipitated during the reaction was filtered and washed with methylene chloride and water at 60° C. to obtain 833 mg (31%) of compound A-1.

[0126] The resulting powder 1 The H-NMR analysis results are as follows, and it was confirmed that the orange powder obtained above was compound A-1. 1 H-NMR(CDCl3(d=ppm)):8.43(s,2H),7.92-7.98(m,6H),7.86(d,2H),7.52-7.61(m,4H),3.45(s,6H)

[0127] [ka]

[0128] To further increase the purity of the compound, sublimation purification was performed. A metal container containing compound A-1 (588 mg) with an LC-MS purity of 97.5% or higher was placed in a glass tube, and 4.2 × 10 -3 The mixture was heated at 250°C under a pressure of 100 Pa and sublimated. 385 mg of the solid adhering to the glass tube wall was collected and analyzed by LC-MS, revealing a purity of 99.6%. The thin film absorption properties of A-1 after sublimation purification were evaluated using the method described above, and the results are shown below. Absorption spectrum (thin film): λmax 520nm Half width: 100nm Next, a photosensor was produced using compound A-1 as a green light absorbing material. A 46 mm x 38 mm transparent glass substrate having an ITO electrode layer with a thickness of 125 nm as an anode was prepared. This substrate was immersed in pure water and ultrasonically cleaned for 10 minutes, then ultrasonically cleaned with isopropyl alcohol for 10 minutes, and thoroughly dried. Then, UV ozone cleaning was performed for 20 minutes.

[0129] Next, a solution of poly(4-styrenesulfonic acid)-doped poly(3,4-ethylenedioxythiophene) (PEDOT:PSS) and isopropyl alcohol in a volume ratio of 6:4 was spin-coated at 3,000 rpm for 30 seconds onto the ITO electrode layer of the substrate, and then heated on a hot plate at 150°C for 10 minutes to form a hole extraction layer with a thickness of 55 nm.

[0130] The substrate on which the hole extraction layer was formed was placed in a vacuum deposition apparatus (manufactured by Eiko Engineering Co., Ltd.) and deposited with approximately 3 × 10 -3 The pressure was reduced to 100 Pa. On the hole extraction layer, N-[1,1'-biphenyl]-4-yl-9,9-dimethyl-N-[4-(9-phenyl-9H-carbazol-3-yl)phenyl]-9H-fluorene-2-amine (60 nm) was evaporated as a hole transport layer. Then, A-1 (23 nm) was evaporated as a p-type organic semiconductor and fullerene (C 60 , 23 nm) were evaporated to form a photoelectric conversion layer.

[0131] After opening the vacuum deposition device to the atmosphere, the deposition source was replaced and the deposition was again carried out at about 3 × 10 -3 The pressure was reduced to 100 Pa. Lithium quinolinol (7.5 nm) and aluminum (74 nm) were sequentially evaporated onto the photoelectric conversion layer to form an electron transport layer and a cathode, respectively. The resulting laminate was sealed with a barrier film (manufactured by TESA) in a glove box to obtain a photosensor.

[0132] The obtained photosensor was evaluated by the above-mentioned method and was found to have sensitivity in the green light region, with an external quantum efficiency of 5.4% and a spectral sensitivity peak wavelength of 508 nm.

[0133] Example 2 Synthesis of Compound A-2 The following reaction was carried out under a nitrogen atmosphere. Compound A-2 was obtained in the same manner as Compound A-1, except that Compound A-1C (2.53 g) obtained above was used as the starting material and iodoethane (1.30 mL) was used instead of iodomethane.

[0134] The resulting powder 1 The H-NMR analysis results are as follows, and it was confirmed that the orange powder obtained above was compound A-2. 1 H-NMR(CDCl3(d=ppm)):8.41(s,2H),7.99(dd,4H),7.89(dd,4H),7.58(brs,4H),3.90-3.96(m,4H),1.26-1.32(m,6H)

[0135] [ka]

[0136] To further increase the purity of the compound, sublimation purification was performed. A metal container containing compound A-2 (1.39 g) with an LC-MS purity of 93.3% or higher was placed in a glass tube, and 5.8 × 10 -3 The mixture was heated at 250°C under a pressure of 1.24 Pa and sublimated. 1.24 g of the solid adhering to the glass tube wall was collected and analyzed by LC-MS, revealing a purity of 99.0%. The thin film absorption properties of A-1 after sublimation purification were evaluated using the method described above, and the results are shown below. Absorption spectrum (thin film): λmax 505nm Half width: 102nm An optical sensor was produced in the same manner as in Example 1, except that compound A-2 was used as the green absorbing material instead of compound A-1, and the thickness of the lithium quinolinol film was set to 9 nm.

[0137] The obtained photosensor was evaluated by the above-mentioned method and was found to have sensitivity in the green light region, with an external quantum efficiency of 1.6% and a spectral sensitivity peak wavelength of 504 nm.

[0138] Comparative Example 1 Compound B-1 was synthesized in the same manner as in the synthesis of compound A-1C, except that cyanobenzene was used instead of compound A-1B.

[0139] [ka]

[0140] To further increase the purity of the compound, sublimation purification was performed. A metal container containing compound B-1 (1.47 g) with an LC-MS purity of 99.4% or higher was placed in a glass tube, and 2.4 × 10 -3 The mixture was heated at 290°C under a pressure of 10 Pa to cause sublimation. At this time, the entire amount of compound B-1 did not sublimate. 440 mg of the solid adhering to the glass tube wall was collected and analyzed by LC-MS, and the purity was 92.8%. In addition, 944 mg of the unsublimed solid was collected and analyzed by LC-MS, and the purity was 98.4%.

[0141] From the above, it was suggested that compound B-1 has poor sublimability, decomposition occurs during sublimation, and has low heat resistance, and is unsuitable for device fabrication by vapor deposition.

[0142] Comparative Example 2 Compound B-2 was synthesized in the same manner as in the synthesis of compound A-1, except that compound B-1B was used instead of compound A-1B and 4-tert-butylbenzyl chloride was used instead of iodomethane in the synthesis of compound A-1.

[0143] [ka]

[0144] To further increase the purity of the compound, sublimation purification was performed. A metal container containing compound B-2 (790 mg) with an LC-MS purity of 98.0% or higher was placed in a glass tube, and 4.0 × 10 -3 The mixture was heated at 260°C under a pressure of 100 Pa and sublimated. 418 mg of the solid adhering to the glass tube wall was collected and analyzed by LC-MS, revealing a purity of 99.5%. The thin film absorption properties of B-2 after sublimation purification were evaluated using the method described above, and the results are shown below. Absorption spectrum (thin film): λmax 455nm Half width: 88nm.

[0145] From the above results, R of the compound represented by the above general formula (1) 3 and R 4 In contrast, it can be seen that a compound in which an α-naphthyl group is substituted for a β-naphthyl group does not selectively absorb green light at the maximum absorption wavelength.

[0146] Example 3 Synthesis of compound A-3 The following reaction was carried out under a nitrogen atmosphere. Compound A-3A (13.25 g), compound A-3B (15.19 g, 16.0 mL), and acetic acid (0.49 mL) were dissolved in toluene (500 mL) and stirred for 6 hours under heating and reflux conditions using a Dean-Stark apparatus. The reaction solution was concentrated under reduced pressure, and the precipitated solid was filtered while being washed with heptane to obtain 20.15 g of A-3C as a pale yellow solid.

[0147] The following reaction was carried out under a nitrogen atmosphere. Compound A-3C (19.9 g) and compound A-1A (7.0 g, 7.1 mL) obtained above were dissolved in dimethylformamide (90 mL) and cooled to -17°C. Sodium tert-butoxide (5.0 g) was gradually added to the reaction solution, which was then warmed to room temperature and stirred for 3 hours. The reaction solution was quenched with acetic acid, ethanol, and water, and the precipitated solid was filtered off. The solid was washed with hot methanol and hot ethanol to obtain 9.1 g of compound A-3D as a pale yellow solid.

[0148] The following reaction was carried out under a nitrogen atmosphere. Compound A-3D (9.0 g) and DDQ (18.7 g) obtained above were dissolved in o-dichlorobenzene (175 mL) and stirred under heating and refluxing conditions for 27 hours. After cooling the reaction solution to room temperature, it was diluted with methylene chloride and DDQ was quenched with activated alumina. The solution was concentrated under reduced pressure, and the precipitated solid was dissolved in methylene chloride, and insoluble solids were removed by suction filtration. Furthermore, silica gel column chromatography was performed using methylene chloride as a developing solvent, and then the solvent was distilled off, and the precipitated solid was washed with hot methanol. The solid was dissolved in 1,2-dichloroethane, and methanol was added to precipitate a red solid. The solid was collected by suction filtration, washed with methanol, and dried under reduced pressure to obtain 314 mg of compound A-3.

[0149] The obtained compound A-3 1 The H-NMR analysis results are as follows, and it was confirmed that the red powder obtained above was compound A-3. 1 H-NMR(CDCl3(d=ppm)):8.50(s,2H),7.77(dd, 4H),7.68(d,2H),7.58-7.40(m,10H),7.20(d,4H),1.33(s,18H)

[0150] [ka]

[0151] The thin film absorption characteristics of the obtained A-3 were evaluated by the above-mentioned method, and the results are shown below. Absorption spectrum (thin film): λmax 528nm Half width: 105nm An optical sensor was produced in the same manner as in Example 1, except that compound A-3 was used as the green absorbing material instead of compound A-1.

[0152] The obtained photosensor was evaluated by the above-mentioned method and was found to have sensitivity in the green light region, with an external quantum efficiency of 5.7% and a spectral sensitivity peak wavelength of 516 nm.

[0153] Example 4 Except for not forming a hole extraction layer, an optical sensor was produced in the same manner as in Example 3. When the obtained optical sensor was evaluated by the above-mentioned method, it showed sensitivity in the green light region, an external quantum efficiency of 6.1%, and a spectral sensitivity peak wavelength at that time of 520 nm.

Claims

1. An electron donor type photoelectric conversion material having a structure represented by the following general formula (1): 【Chemistry 1】 (In the above general formula (1), R 1 and R 2 are each independently selected from the group consisting of a hydrogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted cycloalkyl group, a substituted or unsubstituted aryl group, a substituted or unsubstituted heteroaryl group, and a ring structure between adjacent groups. X 1 and X 2 each independently represents an oxygen atom, a sulfur atom, or a selenium atom. R 3 and R 4 are each independently a group represented by the following general formula (2). 【Chemistry 2】 In the above general formula (2), *** represents a bond to a carbon atom. R 5 ~R 11 are each independently selected from the group consisting of a hydrogen atom, an alkyl group, a cycloalkyl group, an alkoxy group, an alkylthio group, an amino group, an aryl group, a heteroaryl group, an aryl ether group, an aryl thioether group, a silyl group, and a ring structure between adjacent groups. These groups may further have a substituent. )

2. In the general formula (2), R 5 and R 11 2. The electron donor type photoelectric conversion material according to claim 1, wherein at least one of said groups is a hydrogen atom.

3. In the general formula (1), R 1 and R 2 are each independently selected from the group consisting of a substituted or unsubstituted alkyl group, a substituted or unsubstituted cycloalkyl group, a substituted or unsubstituted aryl group, a substituted or unsubstituted heteroaryl group, and a ring structure between adjacent groups.

4. A photoelectric conversion element having a photoelectric conversion layer between an anode and a cathode, which converts light into electrical energy, wherein the photoelectric conversion layer contains the electron donor type photoelectric conversion material according to any one of claims 1 to 3.

5. The photoelectric conversion element according to claim 4 , wherein the photoelectric conversion layer further contains an electron acceptor type photoelectric conversion material.

6. An optical sensor comprising the photoelectric conversion element according to claim 4.

7. A display device comprising the optical sensor according to claim 6 and an organic light-emitting element, the display device having a function of detecting biological information by utilizing light from the organic light-emitting element.

8. The display device according to claim 7 , wherein the biometric information is fingerprint information.

9. The display device according to claim 7 , wherein the biometric information is vein information.

10. A compound having a structure represented by the following formula (3): 【Chemistry 3】 (In formula (3), R 12 ~R 21 are each independently selected from the group consisting of a hydrogen atom, an alkyl group, and an alkoxy group.

Citation Information

Patent Citations

  • Material for photovoltaic element, and the photovoltaic element

    JP2008166339A

  • Material for photoelectric conversion element, and photoelectric conversion element

    JP2010192782A

  • Photoelectric conversion element, imaging element, optical sensor

    WO2014050764A1